Depressurization-induced changes in memory effect of hydrate reformation correlated with sediment morphology. (15th February 2021) - Cheng, Chuanxiao; Wang, Fan; Qi, Tian; Xu, Peiyuan; Zhang, Quanguo; Zhang, Zhiping; He, Chao; Zhang, Jun; Zheng, Jili; Zhao, Jiafei; Zhang, Hanquan; Xiao, Bo
Abstract: Research on the memory effect can improve the rate and efficiency of hydrate reformation, which has important applications in gas hydrate technology. Depressurization is the most widely used gas hydrate dissociation method; however, studies on the mechanism of depressurization on memory effect are still lacking. In this study, the memory effects were compared and analyzed after the hydrate sediment was subjected to different dissociation patterns. The different dissociation patterns included depressurization (different backpressures: 4.5, 3.5, 2.5, 1.5, and 0.1 MPa) and single thermal stimulation dissociation pattern (STSP). The effect of depressurization-induced sediment morphology changes on hydrate-memory effect and gas conversion was obtained under different backpressures. The results indicated that the memory effect tended to remain stable in the STSP, but changed with depressurization dissociation. The memory effect after depressurization dissociation gradually weakened with decreasing backpressure. Notably, an anomalous memory effects was observed, wherein the memory effect was not weakened, but significantly enhanced after depressurization dissociation at 0.1 MPa. Furthermore, depressurization may not only change the memory effect but could also increase the stable interval of the memory effect and the supercooling degree. The average gas conversion ratio of stable interval after dissociation at 0.1 MPa decreased by nearly 8%. Highlights: Changes in memory effect by depressurization and thermal stimulation were compared. The mechanism of the memory effect was obtained under different backpressures. The memory effect was weakened by the escaped gases caused by depressurization. The lower the backpressure, the more the memory effect was weakened. The memory effect was not weakened, but rather was strengthened at 0.1 MPa.